TABOT TRADITION AND ACCULTURATIVE RELIGIOUS TRADITION OF THE BENGKULU COMMUNITY - Khairuddin, Khairuddin; Man, Yovenska L. (UIN Sumatera Utara, 2023)
Abstract: This article aims to explain the Tabot tradition and its cultural construction with the Bengkulu people as a minority group. The Tabot tradition experienced a kind of acculturation process in which two or more cultures met and made contact. Using Berry’s acculturation theory with a qualitative approach and ethnographic methods, this study resulted in a finding that the Tabut tradition resulted from a process of cultural acculturation between different religious and cultural contacts. In its journey, the Tabot is no longer a non-formal tradition but has become a local Bengkulu community organisation with the formation of the Tabot Harmony Family (KKT). The strategy chosen by KKT is to maintain its cultural and community heritage is integration. In this context, integration means maintaining the original culture and cultural contact.Keywords: Tabot, religious-cultural traditions, local Islam, acculturation